IMPROVING THE SEVENTH GRADE STUDENTS’ VOCABULARY MASTERY THROUGH WORD SEARCH PUZZLE AT SMP TRISAKTI 1 MEDAN - Pandiangan, Edinopa; Sembiring, Novalina; Pangaribuan, Jontra Jusat (Kairos English Language Teaching Journal, 2020)
Vocabulary is one of components in the language learning because it is the basic for the people to speak the language. Therefore this study was conducted to improve studentsâ€™ vocabulary mastery by applying Word Search Puzzle. This research design is classroom action research. The subjects of this research were the seventh grade of SMP Trisakti 1 Medan. The result showed in cycle I, there were 5 students (15,63%) whose vocabulary scores had achieved that the target of indicator with mean score is 52,89 (KKM 70) and there were 27 students (78,13%) whose scores were still far from the target. As there were 27 students whose scores below the target, so the indicator of the research had not been fulfilled yetÂ in the first cycle. Nevertheless, in order to fulfill the indicator which is 75% student must be able to get score 70 or more, so the next cycle was conducted. From data in cycle II, there were only 5 students (22%) whose scores were still far from target. In other hand, total students who could get the target are 27 students (78%) with mean score 87,10. Moreover, there is significant improvement from pre-test and post-test. It means that they were good enough in vocabulary after being taught through Word Search Puzzle. The result of this resesarch also shows that studentsâ€™ response after being taught through Word Search Puzzle is good. It can be stated that Word Search Puzzle can improve the studentsâ€™ vocabulary mastery at SMP Trisakti 1 Medan.